2015
DOI: 10.1097/rhu.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Association of Regional and Cultural Factors With the Prevalence of Rheumatoid Arthritis in the Mexican Population

Abstract: Various individual and regional factors were associated with variations in the prevalence of RA in the Mexican population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…One of the hypotheses informing this research was that belonging to the indigenous population is a risk factor on its own for having rheumatic disease. However, our analysis revealed that speaking an indigenous language is also a borderline risk factor [ 32 ]. Although these results are not conclusive, we deem it justifiable to continue studies so as to properly assess indigenous populations in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…One of the hypotheses informing this research was that belonging to the indigenous population is a risk factor on its own for having rheumatic disease. However, our analysis revealed that speaking an indigenous language is also a borderline risk factor [ 32 ]. Although these results are not conclusive, we deem it justifiable to continue studies so as to properly assess indigenous populations in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…In Latin American (LA), previous studies have shown that people belonging to an indigenous group are associated with the prevalence of rheumatic disease as the rheumatoid arthritis (RA) [28]. Due to the presence in LA of indigenous groups, all countries and their condition of vulnerability, not only socioeconomic but also ethnic, were created the Latin American Group for the Study of Rheumatic Diseases in Original Populations (Grupo Latino Americano De estudio de Enfermedades Reumáticas en Pueblos Originarios; GLADERPO).…”
Section: Resultsmentioning
confidence: 99%
“…RA affects 1 % of the world’s population [1], and its prevalence among Mexicans is 1.6 % [2]. RA inflames the synovial membrane of diarthrodial joints and damages the articular tissues, leading to severe functional disarrangement of the entire joint.…”
Section: Introductionmentioning
confidence: 99%